30-day all-cause mortality rate amongst older patients admitted to the medical ward of a tertiary hospital in Nigeria. (2021)
Introduction: Older people face challenges in the overburdened health‑care services in Nigeria, especially when hospitalised. Few available studies on mortality were retrospective, oftentimes with incomplete data which may affect the establishment of the outcome. Objectives: This study determined the 30‑day all‑cause mortality rate (MR) and associated factors amongst older patients in the medical wards of University College Hospital, Ibadan. Materials and Methods: A prospective cohort study of 417 patients (>60 years) from the 1st day of admission to death or discharge at the end of 30th day of admission. Data were collected with a semi‑structured questionnaire. Information obtained included respondents’ sociodemographic characteristics, anthropometric measurements, frailty and functional status. Others were morbidity profile, quality of life, cognition, nutrition, anxiety and depression. Data were analysed using SPSS version 24 at a level of significance P < 0.05. Results: The mean age was 71.6 ± 8.1 years and 216 (51.8%) were females. Eighty‑seven (20.9%) deaths were recorded. The unadjusted 30‑day all‑cause MR was 13.7 deaths (95% confidence interval [CI]: 11.0–16.9/1000 patient‑days). This was significantly higher amongst males than females with a MR ratio (MRR) of 1.93 ([95% CI: 1.23–3.05]; P = 0.01). Factors significantly associated with mortality were being financially self‑supporting (MRR = 2.82; 95% CI: 1.01–6.41), having a cognitive impairment (MRR = 1.92; 95% CI: 1.12–3.20), frailty (MRR = 1.65; 95% CI: 1.01–2.84), ischemic heart disease (MRR = 1.93; 95% CI: 1.18–3.07) and acute exacerbation of bronchial asthma (MRR = 3.92; 95% CI: 1.04–9.42). Conclusion: The 30‑day MR was high amongst older patients, especially the males. Modifiable factors contributing to hospital mortality should be addressed at admission.